2004
DOI: 10.1091/mbc.e03-02-0120
|View full text |Cite
|
Sign up to set email alerts
|

Two Motifs Target Batten Disease Protein CLN3 to Lysosomes in Transfected Nonneuronal and Neuronal Cells

Abstract: Batten disease is a neurodegenerative disorder resulting from mutations in CLN3, a polytopic membrane protein, whose predominant intracellular destination in nonneuronal cells is the lysosome. The topology of CLN3 protein, its lysosomal targeting mechanism, and the development of Batten disease are poorly understood. We provide experimental evidence that both the N and C termini and one large loop domain of CLN3 face the cytoplasm. We have identified two lysosomal targeting motifs that mediate the sorting of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 58 publications
(85 reference statements)
6
145
0
Order By: Relevance
“…We have shown that a consensus approach combined with careful analysis of evolutionary data can produce a model which agrees with almost all published experimental data. Previous work had been less confident about the number of possible TM helices, although one model proposed on the basis of experimental findings [13] agrees closely with ours. Our unexpected finding that orthologues of CLN3 might produce different topologies highlight the increasing realization that transmembrane topology may not be as highly conserved between distantly related species as previously thought.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We have shown that a consensus approach combined with careful analysis of evolutionary data can produce a model which agrees with almost all published experimental data. Previous work had been less confident about the number of possible TM helices, although one model proposed on the basis of experimental findings [13] agrees closely with ours. Our unexpected finding that orthologues of CLN3 might produce different topologies highlight the increasing realization that transmembrane topology may not be as highly conserved between distantly related species as previously thought.…”
Section: Resultssupporting
confidence: 86%
“…This region contains two distinctive lysosomal sorting motifs [13] that experimentally must reside in the cytosol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we sought to demonstrate that PfCRT's C-terminus was exposed in the cytoplasm, which would be consistent with localization in the lysosomal membrane. Digitonin was used to selectively permeabilize the plasma membrane without disturbing the integrity of the lysosomal membrane [29]. We demonstrated selective plasma membrane permeabilization using tubulin as a cytoplasmic marker and cathepsin as an intralysosomal marker.…”
Section: Subcellular Localization Of Pfcrt In Hek293 Cellsmentioning
confidence: 99%
“…Cells were incubated for 1 hr at room temperature (RT) with slow agitation with primary antibodies, and for 30 min each with secondary and tertiary reagents, followed by 4 washes in PBS of 5 min each. Selective plasma membrane permeabilization was achieved using the method of Kyttala and coworkers [29]. After the final wash, PBS was replaced by mounting medium (Sigma, MO) and sealed under a plastic coverslip.…”
Section: Visualization Of Pfcrt Expression By Indirect Immunofluorescmentioning
confidence: 99%